To Those Who Have, More Will Be Given? Effects of an Instructional Time Reform on Gender Disparities in STEM Subjects, Stress, and Health - Hübner, Nicolas; Wagner, Wolfgang; Meyer, Jennifer; Watt, Helen M. G. (Frontiers in Psychology, 2022)
Educational reformers all around the globe are continuously searching for ways to make schools more effective and efficient. In Germany, this movement has led to reforms that reduced overall school time of high track secondary schools from nine to eight years, which was compensated for by increasing average instruction time per week in lower secondary school (Grades 5 to 10). Based on prior research, we assumed that this reform might increase gender disparities in STEM-related outcomes, stress, and health because it required students to learn similar content in less amount of time. Therefore, we investigated how the school time reform affected gender disparities at the end of upper secondary school between 2011 and 2013. Specifically, we considered representative data of the last two cohorts who completed lower secondary school before the reform (N = 2,405) and the first two cohorts after the reform (N = 2,413) from the National Educational Panel Study. Potential differences in gender disparities were investigated for upper secondary school outcomes of subject-specific standardized test performance, self-concept, and interest in mathematics, biology and physics, as well as outcomes of school-related stress and health. Overall, we found substantial disparities between girls and boys, which seemed to change little after the reform. Exceptions were the statistically significant gender × reform interactions for one stress dimension (Overload) and two health dimensions (Overburdening and Achievement-related fear) which increased for both boys and girls, but more strongly for girls.